Analysis of anaerobic power in club level young rowers - Cataldo, A.; Cerasola, D.; Russo, G.; Zangla, D.; Traina, M.1 (European Journal of Sport Studies, 2013)
Aim: To date, assessment of the anaerobic components to determine performance in rowers is not part of standard evaluation or monitoring set for training. The aim of this study was to evaluate the relation between anaerobic power output and ergometer rowing performance over 2000 meters, in a group of 14 -17 years old rowers (n = 11).